Sosialisasi Kesadaran Anti-Bullying Berbasis Pembelajaran IPS sebagai Upaya Penguatan Karakter Sosial Siswa di SDN 03 Konda - Saqjuddin Saqjuddin; Erwin Eka Saputra; Chairan Zibar L. Parisu; La Sisi; Nur Haizah Aopmonaim; La Ode Alwahab; Irma Sari; Sartika Sartika (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
Bullying remains a social issue in elementary schools and negatively affects students’ social development and character formation. Preventive efforts are therefore required through educational strategies integrated into classroom learning. This community service program aimed to increase anti-bullying awareness and strengthen students’ social character through social studies (IPS) based learning at SDN 03 Konda. The program employed an educational and participatory approach consisting of preparation, socialization activities, reinforcement through social studies instruction, and evaluation. During the socialization stage, students were introduced to bullying concepts, various forms, and harmful effects on social interaction. These ideas were reinforced by integrating social values such as empathy, respect, cooperation, and responsibility into learning activities. Results indicated improved student understanding of bullying, awareness of respectful behavior, and positive changes in peer interaction. Learning activities connecting social studies content with everyday social experiences promoted meaningful learning and supported internalization of positive social values. In addition, the program strengthened teachers’ roles as facilitators of character education and supported sustainability of anti-bullying values in daily classroom practices. Overall, socialization of anti-bullying awareness through social studies based learning proved effective for creating a safe, inclusive, and supportive elementary school environment.